2005
DOI: 10.1007/s00436-005-1457-9
|View full text |Cite
|
Sign up to set email alerts
|

Control of clinical coccidiosis of calves due to Eimeria bovis and Eimeria zuernii with toltrazuril under field conditions

Abstract: The efficacy of metaphylactic treatment with toltrazuril (Baycox 5% suspension) against natural infections with Eimeria bovis and/or Eimeria zuernii in calves was investigated. The study was conducted with 208 calves on five calf-rearing farms in Germany and the Czech Republic. All participating farms had a notable incidence of coccidiosis. Animals were treated 14 days after stabling in the respective facility. One group was treated with 15 mg toltrazuril/kg body weight, and a second group served as the sham-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 3 publications
(10 reference statements)
1
32
0
5
Order By: Relevance
“…Eimeria bovis and E. zuernii were reported here and they are noted as the most pathogenic species of Eimeria affecting cattle. Even low infectious doses of E. bovis oocysts (10 4 ) and E. zuernii (10 5 ) result in severe haemorrhagic enteritis with weight losses, dehydration or death of heavily infected animals (Mundt et al, 2005;Hermosilla et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Eimeria bovis and E. zuernii were reported here and they are noted as the most pathogenic species of Eimeria affecting cattle. Even low infectious doses of E. bovis oocysts (10 4 ) and E. zuernii (10 5 ) result in severe haemorrhagic enteritis with weight losses, dehydration or death of heavily infected animals (Mundt et al, 2005;Hermosilla et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In order to eliminate coccidian infection, a Baycox 5% prepara-tion was used after the second parasitological stool examination. In the authors' experience, Baycox is effective against the intracellular developmental stages of coccidia and is very effective in treating Isospora suis in piglets; thus, it was the treatment of choice here (Mundt et al 2005). Three days after the use of Baycox, a fourth parasitological stool examination was performed.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, infected calves in all groups had faecal oocyst scores of 3.16 ± 0.739 prior to treatment, which is comparable to the results of Castro-Hermida et al (2001), who reported 3 ± 0.8. In addition to common fluid therapy, we administered toltrazuril that has been used for the treatment of parasitic diseases such as neosporosis and coccidiosis, caused by other apicomplexan parasites (Gottstein et al 2001;Cuteri et al 2005;Epe et al 2005;Mundt et al 2005;Ocal et al 2007). Azithromycin, a macrolide antibiotic used for treatment of toxoplasmosis (Degerli et al 2003), was also tested in this study.…”
Section: Discussionmentioning
confidence: 99%